Sinergi Mahasiswa dan Jamaah Masjid dalam Pelaksanaan KKN Model Pengabdian Masyarakat Terintegrasi - Hamdan Efendi; Atika Sari; Chandy Meisya; Damsir Edil Fitra; Ella Wahyuni; Indah Julia Astarina; Lutfiana Sukmaningrum; Nidia Liandara; Wela Fera Sasti; Wika Nabila (Jurnal Kemitraan Masyarakat, 2024)
Real Work Lectures (KKN) is a form of community service carried out by students as an implementation of the Tri Dharma of Higher Education. During the implementation of KKN in Keban Agung Dusun Later Agung, students synergized with local mosque congregations to carry out integrated service programs. The aim of this program is to comprehensively increase community capacity and welfare through collaboration between students and mosque congregations. The approach used is a participatory approach, by actively involving the community in every stage of program implementation. The results achieved from this program include increasing the capacity of mosque youth in the religious, economic and social fields; development of productive businesses for groups of mothers; as well as increasing public awareness of environmental cleanliness and health. Apart from that, this program has also succeeded in building trust and close collaboration between KKN students and mosque congregations, so that it can become a model for community service programs based on mosques in the future.